Phase 2 Randomized, Placebo-Controlled Clinical Trial of Recombinant Human Growth Hormone (rhGH) During Rehabilitation From Traumatic Brain Injury - Dubiel, Rosemary; Callender, Librada; Dunklin, Cynthia; Harper, Caryn; Bennett, Monica; Kreber, Lisa; Auchus, Richard; Diaz-Arrastia, Ramon (Frontiers in Endocrinology, 2018)
Traumatic brain injury (TBI) is a major cause of death and disability, but there are currently no therapies with proven efficacy for optimizing regeneration of repair during rehabilitation. Using standard stimulation tests, as many as 40 - 50% of survivors of severe TBI have deficiency of one or more pituitary hormones. Of these, the somatotropic axis is the most commonly affected, with Growth Hormone (GH) deficiency affecting approximately 20% of persons with severe TBI. Treatment with recombinant human Growth Hormone (rhGH) is generally effective in reversing the effects of acquired GH deficiency, but there is no evidence documenting functional or neurocognitive improvement after GH replacement in TBI patients. As a consequence, screening for GH deficiency and GH replacement when deficiency is found is not routinely performed as part of the rehabilitation of TBI survivors. Given that most of the recovery after TBI occurs within the first 6-12 months after injury and IGF-1 and GH are part of a coordinated restorative neurotrophic system, we hypothesized that patients will optimally benefit from GH therapy during the window of maximal neuroregenerative activity. We performed a Phase IIa, randomized, double-blind, placebo-controlled feasibility trial of recombinant human Growth Hormone (rhGH), starting at discharge from an inpatient rehabilitation unit, with follow up at 6 and 12 months. Our primary hypothesis was that treatment with rhGH in the subacute period would result in improved functional outcomes 6 months after injury. Our secondary hypothesis proposed that treatment with rhGH would increase IGF-1 levels and be well tolerated. Sixty-three subjects were randomized, and 40 completed the trial. At baseline, there was no correlation between IGF-1 levels and peak GH levels after L-arginine stimulation. IGF-1 levels increased after rhGH treatment, but it took longer than 1 month for levels to be higher than for placebo-treated patients. rhGH therapy was well tolerated. The rhGH group was no different from placebo in the Disability Rating Scale, Glasgow Outcome Scale-Extended, or neuropsychological function. However, a trend towards greater improvement from baseline in Functional Independence Measure (FIM) was noted in the rhGH treated group. Future studies should include longer treatment periods, faster titration of